To shift the function \( f(x) = (x + 1)^3 \) to the left by three units, you need to replace \( x \) with \( x + 3 \) in the function.
Here's the step-by-step transformation:
-
Start with the original function: \[ f(x) = (x + 1)^3 \]
-
Shift to the left by 3 units by replacing \( x \) with \( x + 3 \): \[ f(x) = ((x + 3) + 1)^3 \]
-
Simplify the expression inside the cube: \[ f(x) = (x + 4)^3 \]
So the new function after the shift is: \[ f(x) = (x + 4)^3 \]
In the form you provided, this is: \[ f(x) = (x + 4)^3 + 0 \]
Thus, the values you fill in are: \[ (x + 4)^3 + 0 \]
So, the final answer is: \[ \text{Shifted form: } f(x) = (x + 4)^3 + 0 \]